Avaliar conhecimento gramatical: análise de itens sobre compreensão de dependências referenciais - Batalha, Joana (Revista da Associação Portuguesa de Linguística, 2019)
The present article aims to contribute to a reflection about evaluation of grammatical knowledge in a school context, trying to find out the importance that has been given to the topic of anaphoric relations and, particularly, to referential dependencies in national examinations of Portuguese language. In a documentary study, which is part of a broader research on relations between grammar and reading comprehension (Batalha, 2017), we analyse a set of examinations carried out between 2008 and 2014 to identify and to characterise items that evaluate the comprehension of referential dependencies in reading and, specifically, the identification of antecedents of different types of anaphoric expressions. The information obtained, which includes statistical data on students’ performance on various items, not only shows that referential dependencies are, in general terms, evaluated in examinations, but also that this may still be a problematic area at the end of basic education.